Cancers and immune related diseases associated with Down's syndrome: a record linkage study. - Goldacre, M; Wotton, C; Seagroatt, V; Yeates, D (2004)
OBJECTIVE: To determine the risk of cancers and selected immune related diseases in people with Down's syndrome, relative to risk in other people. DESIGN: Cohort analysis of a linked dataset of abstracts of hospital and death records; results expressed as the ratios of rates of disease in people with and without Down's syndrome. SETTING: The former Oxford health region, England, 1963-1999. SUBJECTS: Cohort of 1453 people with Down's syndrome and cohort of 460,000 people with other conditions for comparison. MAIN OUTCOMES: As expected, the rate ratio for leukaemia was substantially elevated in people with Down's syndrome: it was 19-fold higher (95% confidence intervals 10.4 to 31.5) than the rate in the comparison cohort. For other cancers combined, excluding leukaemia, the rate ratio was not significantly elevated (1.2; 0.6 to 2.2). The risk of testicular cancer was increased (12.0; 2.5 to 35.6), although this was based on only three cases in the cohort of subjects with Down's syndrome. Significantly elevated risks were found for coeliac disease (4.7; 1.3 to 12.2), acquired hypothyroidism (9.4; 3.4, 20.5), other thyroid disorders, and type 1 diabetes mellitus (2.8; 1.0 to 6.1). A decreased risk was found for asthma (0.4; 0.2 to 0.6). CONCLUSIONS: Our data add to the body of information on the risks of co-morbidity in people with Down's syndrome. The finding on asthma needs to be confirmed or refuted by other studies.